2017
DOI: 10.1534/g3.117.041517
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTLs for 14 Agronomically Important Traits inSetaria italicaBased on SNPs Generated from High-Throughput Sequencing

Abstract: Foxtail millet (Setaria italica) is an important crop possessing C4 photosynthesis capability. The S. italica genome was de novo sequenced in 2012, but the sequence lacked high-density genetic maps with agronomic and yield trait linkages. In the present study, we resequenced a foxtail millet population of 439 recombinant inbred lines (RILs) and developed high-resolution bin map and high-density SNP markers, which could provide an effective approach for gene identification. A total of 59 QTL for 14 agronomic tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 38 publications
3
54
0
2
Order By: Relevance
“…Genetic linkage map is the basis for QTL mapping and gene cloning. Its application value depends on the number of markers, the saturation of the map, and the uniformity of the distribution of markers on the map [25]. Therefore, a construction of a high-density linkage map could improve the accuracy of QTL mapping [27].…”
Section: A Novel High-density Linkage Mapmentioning
confidence: 99%
See 3 more Smart Citations
“…Genetic linkage map is the basis for QTL mapping and gene cloning. Its application value depends on the number of markers, the saturation of the map, and the uniformity of the distribution of markers on the map [25]. Therefore, a construction of a high-density linkage map could improve the accuracy of QTL mapping [27].…”
Section: A Novel High-density Linkage Mapmentioning
confidence: 99%
“…It is caused by lethality, partial male or female sterility, gametic selection or zygotic selection and/or pollen spine development [31,33], which become more serious in RIL populations because of genetic drift [31] was associated with both natural and artificial selection for several generations [16,34]. Zhang et al [25] found segregation distortion on Chr6 which was significantly distorted toward Zhanggu which may exist intraspecific hybrid pollen sterility, and they located one gene controlling the high male-sterility QTL combined with previous report [35]. Similarly, Fang et al [16] found two gametocidal genes (Gc) on Chr8 by the distorted loci in two SDRs skewed toward different parents.…”
Section: Segregation Distortionmentioning
confidence: 99%
See 2 more Smart Citations
“…The benefits of using Setaria as a model species include its small genome, reproductive convenience, abundant genetic variation, and the availability of multiple reference genomes 23 26 . Numerous linkage maps have been constructed for foxtail millet using RFLP 27 , 28 , InDel 24 , SSR 29 31 and SNP 23 , 32 markers, and genomic features including segregation distortion (SD) and chromosome translocation have been identified in individual crosses. However, the low density of molecular markers used for linkage analysis in Setaria remains an obstacle for further genetic analysis of this emerging model.…”
Section: Introductionmentioning
confidence: 99%